2020
DOI: 10.1186/s13568-020-01012-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes involved in xylose metabolism of Meyerozyma guilliermondii and their genetic engineering for increased xylitol production

Abstract: Meyerozyma guilliermondii, a non-conventional yeast that naturally assimilates xylose, is considered as a candidate for biotechnological production of the sugar alternative xylitol. Because the genes of the xylose metabolism were yet unknown, all efforts published so far to increase the xylitol yield of this yeast are limited to fermentation optimization. Hence, this study aimed to genetically engineer this organism for the first time with the objective to increase xylitol production. Therefore, the previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 53 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…The xylitol production capability of M. guilliermondii isolated from honeybee samples was better than the previous report of the M. guilliermondii B12 strain isolated from sugarcane bagasse with the maximum xylitol yield of approximately 0.32 g/g [ 68 ]. Recently, the overexpression of XYL1 and knockout of XDH1 genes encoding in M. guilliermondii ATCC6260 promotes xylitol production with specific productivity of 0.27 g/g xylose [ 38 ]. However, the M. guilliermondii MX strain did not show accumulation of extracellular glycerol when exposed to high-salt stress as previously described [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The xylitol production capability of M. guilliermondii isolated from honeybee samples was better than the previous report of the M. guilliermondii B12 strain isolated from sugarcane bagasse with the maximum xylitol yield of approximately 0.32 g/g [ 68 ]. Recently, the overexpression of XYL1 and knockout of XDH1 genes encoding in M. guilliermondii ATCC6260 promotes xylitol production with specific productivity of 0.27 g/g xylose [ 38 ]. However, the M. guilliermondii MX strain did not show accumulation of extracellular glycerol when exposed to high-salt stress as previously described [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…A large amount of evidence indicates that yeasts could be used as a suitable platform for chemical production of valuable metabolites. Some yeast species can produce xylitol as main product, such as Scheffersomyces [ 35 , 36 ], Kluyveromyces [ 37 ] and Meyerozyma [ 38 ]. Recently, Meyerozyma guilliermondii B12 strain has been the best isolated strain from sugarcane bagasse due to its capability to produce xylitol with 0.30 g xylitol/g xylose consumed [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, five genes of the pentose and glucuronate interconversion and two of pentose phosphate pathways were significantly suppressed under glucose compared to growth under xylose. As expected, significant overrepresentation of genes encoding d -xylulose reductase/ l -iditol 2-dehydrogenase (EC:1.1.1.9/EC:1.1.1.14), EHS25_007055 (log2FC = −5.1 and FDR = 2.0 × 10 −51 ) and EHS25_005852 (log2FC = −3.8 and FDR = 4.0 × 10 −31 ), which catalyses the oxidation of xylitol to d -xylulose [ 69 ] was observed in xylose relative to glucose ( Figure 5 a). Xylulokinase (EC:2.7.1.17), EHS25_008536 (log2FC = −4.7 and FDR = 5.0 × 10 −37 ), which catalyses xylulose to xylulose-5-phosphate phosphorylation was also overrepresented under xylose.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study in protoplast fusion between S. cerevisiae and P. stipitis obtained fusant, fusant which appear decrease in bioethanol production compare with a parent were selected for current study on xylitol production. [4] reported that Meyerozyma guilliermondii, a non-conventional yeast, is being considered as a biotechnological candidate for xylitol processing. This is in agreement with the aforementioned [33] about the improvement of xylitol production from sugarcane bagasse by using phylogenetically identified as Pichia fermentans isolated from a chemical mutagenesis using ethyl methanesulfonate (EMS).…”
Section: Xylitol Production From Batch Fermentation Of Hydrolase Hemicellulose Using Meyerozyma Guilliermondii Strain F22mentioning
confidence: 99%